Water quality and heavy metal concentrations in sediment of Sunagi Kelantan,Kelantan,Malaysia:A baseline study - Ahmad A.K; Mushrifah I; Mohamad Shuhaimi Othman (Universiti Kebangsaan Malaysia, 2009)
A study on water quality and heavy metal concentration in sediment at selected sites of Sungai Kelantan was carried out. Ten water samples were collected along the river for physical and chemical analysis and twenty-six water and sediment samples were collected for heavy metal analysis. Water was sampled at three different dates throughout the study period whereas sediments were collected once. In addition to heavy metal analysis, sediment samples were also analysed for texture, pH and organic content. The physical and chemical water quality analyses were carried out according to the APHA procedures. Result of water quality analysis (physico-chemical) indicated that Sungai Kelantan is characterised by excellent water quality and comparable to pristine ecosystems such as the National Park and Kenyir Lake. This river was classified into class I – class III based on Malaysian interim water quality standard criteria (INWQS). Heavy metals Pb, Zn, Cu and Cd was detected at low concentration in sediment samples, except for Fe and Mn. The presence of Fe and Mn in sediment samples was though to be of natural origin from the soil. Anthropogenic metal concentrations in sediment were low indicating that Sungai Kelantan has not experienced extreme pollution.